1998
DOI: 10.1021/bi981591x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for p38 Protein Kinase Inhibitor Specificity

Abstract: p38 is a member of the mitogen-activated protein (MAP) kinase family and is a critical enzyme in the proinflammatory cytokine pathway. Other MAP kinase group members that share both structural and functional homology to p38 include the c-Jun NH2-terminal kinases (JNKs or SAPKs) and the extracellular-regulated protein kinases (ERKs). In this study, we determined the molecular basis for p38alpha inhibitor specificity exhibited by five compounds in the diarylimidazole, triarylimidazole, and triarylpyrrole classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 37 publications
1
69
0
Order By: Relevance
“…1). Compound 1 is structurally similar to known protein kinase inhibitors (29,30,39,40) and we show here that this compound does inhibit a kinase in the parasite, namely PKG. Like other protein kinase inhibitors, Compound 1 is competitive with respect to ATP.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…1). Compound 1 is structurally similar to known protein kinase inhibitors (29,30,39,40) and we show here that this compound does inhibit a kinase in the parasite, namely PKG. Like other protein kinase inhibitors, Compound 1 is competitive with respect to ATP.…”
Section: Discussionmentioning
confidence: 61%
“…Compound 1-binding Protein Is a cGMP-dependent Protein Kinase-The structural similarity between Compound 1 and protein kinase inhibitors that have been described in the literature (29,30) prompted us to assay for and detect kinase activity (using the peptide substrate Kemptide) in the ligand binding fractions during the purification protocol. However, protein kinase activity was marginal (data not shown), even in the final fractions from the MonoQ column pictured in Fig.…”
Section: Antiparasitic Activity Of Compound 1-thementioning
confidence: 99%
“…Previous in vitro studies demonstrated that replacement of Thr 106 with Met in p38␣ had no measurable affect on enzymatic activity but decreased the affinity of certain p38 inhibitors by several orders of magnitude (25)(26)(27)(28). We generated in vivo models to study the specific roles of these p38 isoforms by creating genetically engineered mice expressing a Thr 106 to Met substitution in either p38␣ or p38␤.…”
Section: Discussionmentioning
confidence: 99%
“…SB203580, a member of this group, is a highly selective inhibitor of p38 MAPK, which does not alter the activity of other MAPKs including ERKs and JNKs (41)(42)(43). We thus used this inhibitor to investigate the role of p38 MAPK activity in invasion of BT549 breast cancer cells.…”
Section: Endogenous P38 Mapk Activity Is Associated With Breastmentioning
confidence: 99%